Explaining the Gender Gap in Financial Literacy: The Role of Non‐Cognitive Skills. (6th December 2017) - Arellano, Alfonso; Cámara, Noelia; Tuesta, David
Abstract : Economic literature identifies a gender gap in financial literacy. This paper tests to what extent this gender gap is due to a misspecification problem or whether it exists because boys and girls do indeed have differing ways of acquiring financial literacy. Our estimates show that the gender gap decreases by 20 per cent when the model includes the effect of non‐cognitive skills, for 15‐year‐old students in Spain. However, differences between boys and girls in financial literacy remain statistically significant.